CHALLENGES AND SOLUTIONS FOR SUSTAINABLE URBAN MOBILITY: LESSONS FROM AMSTERDAM AND CURITIBA - Fábio Friol Guedes de Paiva; Ana Beatriz Montanha Elias; Ana Clara Wiezorek Pires; Maria Eduarda Breda; Nathalia Ramsdorf Ponciano (Mix Sustentável)
The significance of sustainable urban mobility has become increasingly apparent, emerging as a priority in addressing contemporary environmental challenges. Frequent congestion in major urban centers, coupled with pollution from combustion-based transportation, exacerbates global warming. These challenges necessitate a reevaluation of urban transport systems and the implementation of measures that foster more sustainable and equitable mobility. Such measures include the development of dedicated cycling infrastructure and the enhancement of public transportation to increase its appeal and efficacy. This study examines sustainable urban mobility solutions in Curitiba and Amsterdam through bibliographic and descriptive research. The findings indicate that a well-planned road system can significantly reduce travel time, enhance quality of life, and alleviate the stress associated with daily transportation. Moreover, public policies that promote the use of bicycles and electric vehicles are essential in advancing sustainable mobility. The study concludes that planning measures aligned with sustainability have positive impacts on traffic flow, population well-being, and the environment